Neuroprotective Activity of Melittin-The Main Component of Bee Venom-Against Oxidative Stress Induced by Aβ25-35 in In Vitro and In Vivo Models - Cong Duc Nguyen; Gihyun Lee (MDPI AG, 2021)
Melittin, a 26-amino acid peptide, is the main component of the venom of four honeybee species and exhibits neuroprotective actions. However, it is unclear how melittin ameliorates neuronal cells in oxidative stress and how it affects memory impairment in an in vivo model. We evaluated the neuroprotective effect of melittin on Aβ25-35-induced neuro-oxidative stress in both in vitro HT22 cells and in vivo animal model. Melittin effectively protected against HT22 cell viability and significantly deregulated the Aβ25-35-induced overproduction of intracellular reactive oxygen species. Western blot analysis showed that melittin suppressed cell apoptosis and regulated Bax/Bcl-2 ratio, as well as the expression of proapoptotic related factors: Apoptosis-inducing factor (AIF), Calpain, Cytochrome c (CytoC), Cleaved caspase-3 (Cleacas3). Additionally, melittin enhanced the antioxidant defense pathway by regulating the nuclear translocation of nuclear factor erythroid 2-like 2 (Nrf2) thus upregulated the production of the heme oxygenase-1 (HO-1), a major cellular antioxidant enzyme combating neuronal oxidative stress. Furthermore, melittin treatment activated the Tropomyosin-related kinase receptor B (TrkB)/cAMP Response Element-Binding (CREB)/Brain-derived neurotrophic factor (BDNF), contributing to neuronal neurogenesis, and regulating the normal function of synapses in the brain. In our in vivo experiment, melittin was shown to enhance the depleted learning and memory ability, a novel finding. A mouse model with cognitive deficits induced by Aβ25-35 intracerebroventricular injection was used. Melittin had dose-dependently enhanced neural-disrupted animal behavior and enhanced neurogenesis in the dentate gyrus hippocampal region. Further analysis of mouse brain tissue and serum confirmed that melittin enhanced oxidant-antioxidant balance, cholinergic system activity, and intercellular neurotrophic factors regulation, which were all negatively altered by Aβ25-35. Our study shows that melittin exerts antioxidant and neuroprotective actions against neural oxidative stress. Melittin can be a potential therapeutic agent for neurodegenerative disorders.